Effect of component content variation on composition and structure of activated carbon in PVDF:K2CO3. Issue 5 (16th January 2019) - Zhu, Wenliang; Okada, Kohei; Li, Zhong; Zhu, Jiliang; Marin, Elia; Pezzotti, Giuseppe
Abstract : Percolative composites consisting of potassium carbonate dispersed in polyvinylidene fluoride (PVDF) polymeric matrix have shown high dielectric constant and electrical conductivity due to the formation of chemically activated carbon interfaces in the composite. Abstract : Percolative composites consisting of potassium carbonate dispersed in polyvinylidene fluoride (PVDF) polymeric matrix have shown high dielectric constant and electrical conductivity due to the formation of chemically activated carbon interfaces in the composite. In this paper, a series of PVDF/K2 CO3 films with different component contents were prepared and investigated by Raman and X-ray photoelectron spectroscopies to clarify chemical composition, structure and formation mechanism of activated carbon. The results revealed the presence of a reaction loop to consume both constituent phases and the formation of sp 2 carbon rings in the yielded activated carbon due to cross-linking dehydrofluorination of PVDF during thermal treatment. The sp 2 content showed a non-linear dependence on K2 CO3 content with the presence of an optimal value corresponding to the highest dielectric constant and electrical conductivity. This study thus can give a direction for future fabrication of PVDF/K2 CO3 electrode materials for supercapacitors.